An evaluation of human immunodeficiency virus oral screening test awareness and preferences in the West region of Cameroon - Nkenfou, C.N.; Kembou, J.T.; Djikeng, Appolinaire; Domkam, I.; Tchuinkam, T. (Elsevier, 2015)
HIV serological diagnosis has evolved during the last decade to give rise to rapid testing using biological materials, such as blood or oral mucosal transudate (OMT). However, blood collection is not always welcomed, justifying the evaluation of OMT-based devices. In a cross sectional study carried out in May 2011 aimed at evaluating the level of awareness about OMT based HIV tests, questionnaires were administered to participants who consented to take part in the study. Eighty-five percent (n = 1520) of participants reported a lack of awareness of HIV oral screening before the study, and surprisingly, no association was found between the awareness of participants and their educational level (p = 0.768). There was also no association (p = 0.743) found between having had previous screening tests and awareness of oral testing. The percentage of participants who accepted the oral test before being informed about it was 31.3% (n = 1520). After sensitization, 76.3% (n = 1520) preferred oral screening for future tests (p = 0). These results reveal that if the OMT based test is affordable, its implementation as a screening tool in the general population could greatly increase participation in screening campaigns and is welcomed by those who want to self-test in a non-invasive way. This will create a better estimation of the national HIV prevalence. Its use could then have a significant public health impact on HIV prevention and clinical management.C